Penerapan program latihan circuit training dan tabata workout terhadap tingkat kebugaran jasmani dan indeks massa tubuh - Tarigan, Ananda Rizky; Ujang Rohman; Santika Rentika Hadi (Physical Education Departement of University PGRI Jombang, 2025)
Due to the advancement of technology and the rise in sedentary lifestyles, which have a detrimental effect on physical health, adolescent health issues have gained prominence. Students in the tenth grade at SMA Santa Maria Surabaya also exhibit this phenomenon, with low levels of physical fitness and tendencies toward obesity. This study uses the Tes Kebugaran Pelajar Nusantara (TKPN) pretest–posttest design to assess the effects of two exercise models, Tabata Workout and Circuit Training, on students' physical fitness and Body Mass Index (BMI). Direct observation, documentation, and fitness evaluations were used to gather data. To ascertain the significance of differences prior to and following the intervention, t-test statistical techniques were applied to the pretest and posttest data. The findings indicated that for physical fitness, Tabata Workout yielded t = –1.638 (p = 0.110) and Circuit Training yielded t = –0.957 (p = 0.345), with all p-values exceeding 0.05, suggesting no significant improvement. For BMI, the Tabata Workout recorded t = 0.290 (p = 0.773), while Circuit Training recorded t = 0.612 (p = 0.544), both indicating no statistical significance. While minor increases were noted in certain fitness components, these alterations did not achieve statistical significance. Consequently, neither exercise program demonstrated significant enhancements in physical condition. The findings indicate that adolescent health issues constitute a significant challenge, necessitating physical exercise interventions that are structured, intensive, and tailored to the specific needs of students.